Synthetic sweeteners and their impact on the gut microbiota - current state of knowledge - Karolina Wąsik; Sebastian Tomaszuk; Magda Wojtuś (Kazimierz Wielki University, 2023)
Introduction and purpose: The aim of artificial sweeteners is to replace the sweetness of sugar without contributing to the higher energy consumption or unfavorable metabolic effects conventional sugar causes. Synthetic sweeteners - one of the most popular groups - are labeled as safe for use in foods and represented by acesulfame K, aspartame, neotame, saccharin, sucralose, cyclamate and advantame. Although they underwent safety procedures, their possible unbeneficial effects are still being evaluated. In this paper we focus on their impact on the gut microbiome. Brief description of the state of knowledge: For now, the advantage of search conducted on animals is observed. Those papers show the possibility of a  relationship between artificial sweeteners and composition of the gut microbiota. Changes that were observed affected the gut microbiota in a negative way as they may be responsible for causing disbalance in the conglomerate of microorganisms. Studies on humans are limited. Long term consumption of acesulfame K and sucralose is linked with modulation of the composition of the microbiota. It has also been shown that synthetic sweeteners are able to  increase the ability of bacteria to form a biofilm.  Conclusions: Heretofore published paperworks about the impact of synthetic sweeteners on the gut microbiota are not sufficient to conduct valuable and unambiguous conclusions. Evidence collected until now is leading to a deduction that gut microbiota can be affected by the consumption of the sugar surrogates although more data is needed to clearly determine their possible role.